15. THE RELATIONSHIP BETWEEN NUTRITION AND SOME SIDE EFFECTS OF HIGH-DOSE METHOTREXATE ON BONE CANCER PATIENTS AT THE PEDIATRIC DEPARTMENT OF K HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe some adverse effects of high-dose Methotrexate regimen in patients with bone cancer and to explore on the relationship between nutritional status and these adverse effects.Materials and methods: A cross-sectional study using a pre-designed questionnaire was conducted in 42 bone cancer patients receiving high-dose Methotrexate at the Pediatric Department of K Hospital, from April 2024 to October 2024.Results: The most common age group for bone cancer was between 10-20 years, comprising 78.4% of the sample, with a higher percentage of male patients (57.1%). Most patients (74.8%) were from rural or mountainous areas. At diagnosis, 21.4% of patients had metastasis, and 33.3% experienced underweight or malnutrition during treatment. The most prevalent clinical symptoms included vomiting, nausea, loss of appetite, and hair loss, which were reported by 81% of patients. Diarrhea was noticed in 19% of patients, while 90.5% of them had leucopenia. Methotrexate toxicity was observed in 52.4% of patients. The malnourished group had higher rates of oral mucositis and MTX toxicity than the healthy group (p values ​​are 0.026 and 0.03, respectively).Conclusion: Patients with bone sarcoma have a high rate of malnutrition at 33.3%. Nutritional status was significantly associated with the adverse effects of MTX, namely stomatitis and methotrexate toxicity.
Keywords: nutrition; high-dose methotrexate; bone cancer